2020
DOI: 10.3389/fpls.2020.00848
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Serine Carboxypeptidase-Like Acyltransferase Gene Family for Evolution and Characterization of Enzymes Involved in the Biosynthesis of Galloylated Catechins in the Tea Plant (Camellia sinensis)

Abstract: Tea (Camellia sinensis L.) leaves synthesize and concentrate a vast array of galloylated catechins (e.g., EGCG and ECG) and non-galloylated catechins (e.g., EGC, catechin, and epicatechin), together constituting 8%-24% of the dry leaf mass. Galloylated catechins account for a major portion of soluble catechins in tea leaves (up to 75%) and make a major contribution to the astringency and bitter taste of the green tea, and their pharmacological activity for human health. However, the catechin galloylation mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 83 publications
1
39
0
Order By: Relevance
“…For the cold treatment experiments, tea plant leaves were collected during the cold acclimation (CA) process. Control (CK): 25 °C; CA 1 -6 h: 10 °C for 6 h; CA 1 -7 days: from 10 °C to 4 °C for 7 days; CA 2 -7 days: from 4 °C to 0 °C for 7 days; DA-7d: recover under 25 °C to 20 °C for 7 days, as described previously 42 . Transcriptome data from experiments with tea cv.…”
Section: Methodsmentioning
confidence: 99%
“…For the cold treatment experiments, tea plant leaves were collected during the cold acclimation (CA) process. Control (CK): 25 °C; CA 1 -6 h: 10 °C for 6 h; CA 1 -7 days: from 10 °C to 4 °C for 7 days; CA 2 -7 days: from 4 °C to 0 °C for 7 days; DA-7d: recover under 25 °C to 20 °C for 7 days, as described previously 42 . Transcriptome data from experiments with tea cv.…”
Section: Methodsmentioning
confidence: 99%
“…These materials were used for metabolite analysis, RNA extraction for transcriptome sequencing or qRT-PCR analysis. Transcriptomic data from various experimental treatments (MeJA, polyethylene glycol, NaCl and cold, and shade) were retrieved from previous studies and the Tea Plant Information Archive ( http://tpia.teaplant.org/index.html ) 43 , 61 63 .…”
Section: Methodsmentioning
confidence: 99%
“…The SCPL gene family plays an important functional role in plants. Whole-genome analysis of SCPL genes has been performed in a variety of plants and allowed for the identification of 71 putative SCPL genes in rice ( O. sativa ), 54 in Arabidopsis ( A. thalianna ), 57 in poplar and 47 in the tea plant ( Camellia sinensis ) [ 52 – 54 ]. However, no systemic analysis of the SCPL gene family has been reported in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic analysis showed that wheat, tea, poplar and Arabidopsis have more genes in the CPI and CPII subfamilies. This indicates that the SCPL s in these different species might be undergoing conservative evolution [ 52 – 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation